Logistics park development in Slovak Republic - Šulgan, Marián (Transport, 2006)
The paper deals with the actual situation in the Slovak Republic concerning the logistics parks development. It presents the theoretical base of the logistics park development, i.e. the comparative analysis, SWOT analysis, transport infrastructure survey, marketing study and marketing plan for logistics park. It also presents the basic characteristic of logistics park, logistics chains and activities connected with the transport, logistics and goods distribution.First Published Online: 27 Oct 2010